Aplikasi Agens Hayati dan Humus untuk Menekan Populasi Fusarium oxysporum f.sp. cubense Penyebab Busuk Batang Pisang - SWANDEWI, NI KADEK LIA; SUDANA, I MADE; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.4, Oktober 2019, 2019)
Application of Biological Agent and Humus to Suppress Population Fusarium oxysporum f.sp. cubense the Cause of Banana Stem Rot. The study aimed to determine the interaction between P. fluorescens, Trichoderma spp. fungus, and humus in suppressing the population of Fusarium oxysporum f.sp. cubense in the soil. The design used was a randomized block design (RBD) of 2 factors namely antagonistic microbes and humus. There were 18 treatments with 3 replications so that 54 experimental units were obtained. The variables observed were the population of Foc, population of P. fluorescens, population of Trichoderma spp., and soil pH. The results showed that the combination of biological agent and humus could reduce the population of Foc. The higher concentration of humus combined with biological agent showed the decreasing population of Foc which causes rot of banana stems.